Data base for water and sanitary plumbing system design - Amorim, Simar Vieira de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Based on a previous study on companies involved in the water and sanitary plumbing system design and construction processes, the structure of an information system was developed, seeking quality improvement of the design stage. Its main core is the compatibility between this and other subsystems design. The second focus of this structure, as suggested by the practitioners from the industry, was to satisfy the need for an information system, which could help in the design inception phase, and not simply in the process rationalisation, production of drawings, and production of the bill of materials. A process flowchart is proposed which contains several databases that the designer should possess. The development of Database B2 (Materials, Equipments and Components) was taken as starting point. This article presents the concepts involved in the design of this database as well as describes its the current stage of development.